Effective bioconversion of locally obtained apple waste into citric acid using aspergillus niger (NRRL 567) - Akhter, Faheem; Aziz, Shaheen; Jalal, Fatima (Penerbit Universiti Kebangsaan Malaysia, 2022)
A viable and sustainable method was used to produce citric acid. Apple waste (pomace) was used as a substrate and displayed a good efficiency for citric acid yield. The fermentation process was carried out using Aspergillus Niger (NRRL 567) strain. This fungal strain showed a competent performance in fermenting apple waste to produce citric acid. Various key parameters were analyzed and optimized such as incubation temperature, amount of substrate, ph, moisture content, nitrogen source, metal ions, methanol inducer and inoculum density. Among such parameters, the highest citric acid yield of 158 g/kg of apple pomace was achieved with the use of methanol inducer. Methanol inducer, moisture content, amount of substrate and nitrogen source were found to have significant impact on CA production. The fungal strain used in the present study is known to possess an impressive biomass fermentation capacity, as also demonstrated by the present work. In Pakistan, this strain has not been analyzed for its efficiency to produce citric acid using pomace of locally cultivated apple, hence the novelty of the present work. All the experimental work, analysis and optimization was accomplished on laboratory scale at Advanced Research Laboratory, Zoology Department, GC University, Faisalabad, Pakistan.